211k views
3 votes
2(a³+b²+11)+1(3+a³+b+11)

User Osmingo
by
6.4k points

1 Answer

4 votes

Answer:


2(a^3+b^2+11)+1(3+a^3+b+11)=3a^3+2b^2+b+36

Explanation:

I assume that you need simplification of the given expression.

The given expression is:


2(a^3+b^2+11)+1(3+a^3+b+11)

Using distributive property and multiplying 2 inside the parenthesis and 1 inside the other parenthesis. This gives,


2(a^3+b^2+11)=2* a^3+2* b^2+2* 11\\2(a^3+b^2+11)=2a^3+2b^2+22\\\\1(3+a^3+b+11)=1* 3+1* a^3+1* b+1* 11\\1(3+a^3+b+11)=3+a^3+b+11=a^3+b+14

Therefore,
2(a^3+b^2+11)+1(3+a^3+b+11) is equal to:


2a^3+2b^2+22+a^3+b+14

Now, combining like terms using the commutative property of addition, we get:


=(2a^3+a^3)+2b^2+b+(22+14)\\=3a^3+2b^2+b+36

Therefore, the simplified form is
3a^3+2b^2+b+36

User Don Albrecht
by
5.8k points